Ethical and Legal Aspects of Organ and Tissue Donation and Transplantation in Venezuela (2018)
Aim: This article carries out a documentary review on organ transplantation and its relations from a legal point of view, building on the international principles governing transplants. It also intends to analyze how this activity is regulated by our substantive legal system. Period covered, origin and types of publications: A search was made on databases and literature described in medicine books, as well as in current legal texts of the Venezuelan legal system with relevant information on the new legislation. Point of view: In medical-legal research, professionals must deal with the sensitive subject of donation and transplantation, which often represents a decisive point because of the imposed presumed consent to organ, tissue and human cell donation and transplantation contained in the new law. Conclusions: In establishing the presumed donation consent, current legal regulations on organ, tissue and cell donation and transplantation create uncertainty about how it operates in practice and tend to violate basic, ethical and legal principles, if we start from a conception based on universal human rights such as the right to health as part of the right to life and the right to self-determination, among others.